Acid sphingomyelinase downregulation alleviates vascular endothelial leptin resistance in rats - Cai Bei-bo; Lu Yi-ni; Xu Ming (Acta Pharmacologica Sinica, 2020)
Leptin resistance in endothelial cells leads to vascular endothelial dysfunction, which is the beginning and crucial link of atherosclerosis. However, the mechanism of leptin resistance remains obscure. Acid sphingomyelinase (ASM) catalyzes the hydrolysis of sphingomyelin to produce ceramide, which plays an important role in the progression of metabolic and cardiovascular diseases. In this study, we investigated whether ASM could regulate leptin resistance in vascular endothelial cells. We induced endothelial leptin resistance in rat aortic endothelial cells through treatment with palmitic acid (0.3 mM) or knockdown of leptin receptor (Ob-Rb), which resulted in the increase of suppressor of cytokine signaling 3 expression, the decrease of Ob-Rb expression, and signal transducer and activator of transcription 3 (STAT3) phosphorylation at Tyr705. We found that these indicators of leptin resistance were reversed by knockdown of ASM or by the selective ASM inhibitors amitriptyline (AMI) and imipramine (IMI). Supplementation of ceramide inhibited Ob-Rb expression and STAT3 phosphorylation by inhibiting extracellular signal-regulated kinase 1/2 activation. Furthermore, we found that knockdown of ASM enhanced endothelial nitric oxide (NO) synthase activity and NO production, as well as the Akt phosphorylation at ser473, which was regulated by STAT3. High-fat diet (HFD) feeding-induced leptin resistance in rats in vivo; administration of AMI and IMI (10 mg· kg−1 per day, intraperitoneally, for 2 weeks) increased the release of endothelial NO to relieve the vasodilatory response and improved the endothelial leptin resistance in the aorta of HFD-fed rats. These results suggest that ASM downregulation reverses endothelial leptin resistance, and consequently improves vascular endothelial dysfunction. This study highlighted ASM as a potential therapeutic target for endothelial leptin resistance.